2017
DOI: 10.1371/journal.pmed.1002407
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary disengagement from antiretroviral therapy in Khayelitsha, South Africa: A cohort study

Abstract: BackgroundRetention in care is an essential component of meeting the UNAIDS “90-90-90” HIV treatment targets. In Khayelitsha township (population ~500,000) in Cape Town, South Africa, more than 50,000 patients have received antiretroviral therapy (ART) since the inception of this public-sector program in 2001. Disengagement from care remains an important challenge. We sought to determine the incidence of and risk factors associated with disengagement from care during 2013–2014 and outcomes for those who diseng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 31 publications
(43 reference statements)
7
91
2
Order By: Relevance
“…Individual and structural reasons for such LTFU identified in the literature could be amplified among OA due to limited autonomy and resources to independently continue ART. Our findings are in line with recent reports which suggest pregnancy at ART initiation is a significant risk factor for LTFU , and that postnatal disengagement from ART services is a significant programmatic challenge . Our observations imply that pregnant OA initiating ART should be one of the key populations targeted for interventions to reduce LTFU in prevention of mother‐to‐child HIV transmission (PMTCT) programmes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Individual and structural reasons for such LTFU identified in the literature could be amplified among OA due to limited autonomy and resources to independently continue ART. Our findings are in line with recent reports which suggest pregnancy at ART initiation is a significant risk factor for LTFU , and that postnatal disengagement from ART services is a significant programmatic challenge . Our observations imply that pregnant OA initiating ART should be one of the key populations targeted for interventions to reduce LTFU in prevention of mother‐to‐child HIV transmission (PMTCT) programmes.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, pregnancy at ART initiation is increasingly being associated with high LTFU after ART initiation in multiple cohorts, particularly as countries adopt lifelong ART for pregnant and breastfeeding women (Option B+) . Reasons for this may include individual factors related to child care, relationships with partners and family, migration postdelivery, stigma, and social barriers .…”
Section: Introductionmentioning
confidence: 99%
“…[3] Eligibility criteria have evolved in response to World Health Organization (WHO) recommendations, with universal test and treat adopted nationally in September 2016. [7]…”
Section: Settingmentioning
confidence: 99%
“…First, our estimates of ART retention are conservative. Previous studies showed that transient treatment interruptions and movements between clinics are common and many patients recorded with LTFU are retained [26,74,75]. Because of limitation in routine monitoring and limited tracking of patients lost to follow-up, this study was not able to adjust for silent transfer between treatment sites and silent return to care.…”
Section: Limitations and Strengthsmentioning
confidence: 97%